Rapid detection of Akabane virus by a novel reverse transcription loop-mediated isothermal amplification assay (RT-LAMP) - Qiao, Jun (BioMed Central, 2013)
BACKGROUND: Akabane disease, caused by Akabane virus, is an insect-transmitted disease of ruminants that is primarily characterized by fetal damage. METHODS AND RESULTS: In this study, a novel reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay for rapid detection of Akabane virus was successfully developed. The primers were designed to target the highly conserved fragment of nucleoprotein from the Akabane virus. The results indicate that the assay is highly specific and sensitive with a detection limit of 5.0 TCID(50) /mL within a 60-min incubation time. A total of 126 abortive samples collected from Xinjiang province were detected by the established RT-LAMP. The results of RT-LAMP assay showed 96.8% agreement with the semi-nested RT-PCR. CONCLUSION: This study is to first to develop a rapid, sensitive, and accurate method for the detection of Akabane virus, which may be used to screen clinical samples in developing countries or regions.